2013
DOI: 10.1371/journal.pone.0066930
|View full text |Cite
|
Sign up to set email alerts
|

RPS19 and TYMS SNPs and Prevalent High Risk Human Papilloma Virus Infection in Nigerian Women

Abstract: High risk HPV (hrHPV) infection is a necessary cause of cervical cancer but the host genetic determinants of infection are poorly understood. We enrolled 267 women who presented to our cervical cancer screening program in Abuja, Nigeria between April 2012 and August 2012. We collected information on demographic characteristics, risk factors of cervical cancer and obtained samples of blood and cervical exfoliated cells from all participants. We used Roche Linear Array HPV Genotyping Test® to characterize the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…However, the results from previous studies have been inconsistent (511). Several pathogens, particularly those capable of establishing persistent infections can affect cellular apoptotic pathways and potentially facilitate abnormal cell growth (12).…”
Section: Introductionmentioning
confidence: 90%
“…However, the results from previous studies have been inconsistent (511). Several pathogens, particularly those capable of establishing persistent infections can affect cellular apoptotic pathways and potentially facilitate abnormal cell growth (12).…”
Section: Introductionmentioning
confidence: 90%
“…In a subsequent study, the investigators examined 18,310 SNPs in 1,113 genes and reported that SNPs in PRDX3 and RPS19 were associated with HPV persistence and progression from persistent HPV infection to CIN3+ (10). We examined the association between the aforementioned SNPs and prevalent hrHPV infection in African women, and successfully replicated RPS19:rs2305809 and TYMS:rs2342700 (11).…”
Section: Introductionmentioning
confidence: 89%
“…We extracted DNA from the cervical exfoliated cells as previously described (11). Samples were tested for HPV DNA by hybridization of SPF 10 amplimers to a mixture of general HPV probes recognizing a broad range of high-risk, low-risk, and possible hrHPV genotypes in a microtiter plate format, as described previously (61).…”
Section: Hpv Detection By Spf 10 /Lipa 25mentioning
confidence: 99%
“…Evidence in LMICs suggests polymorphisms on the TYMS and RPS19 genes are associated with high-risk infection in Nigerian women, but overall in LMICs evidence is lacking on factors influencing effective HPV clearance ( 68 ). Several studies of women in HICs of African ancestry have identified that women of African-American descent despite having a similar prevalence of HPV, take longer to clear the virus ( 69 ).…”
Section: Molecular Diversity Affecting Communicable Causes Of Cancermentioning
confidence: 99%
“…So far, they have largely focussed on communicable disease such as trypanosomiasis, stroke and other neurological diseases affecting patients across the continent. Relevant to the field of oncology, some work has been undertaken into HPV infection in Nigeria ( 68 ), with the women included in this study demonstrating similar genetic susceptibility to infection as other populations. This group are set to expand into the field of breast cancer, which will provide useful data to study the genomic epidemiology of the disease on the African continent.…”
Section: Barriers To Global Research In Precision Medicinementioning
confidence: 99%